The Influence of Acids on Tuning the Pore Size of Mesoporous TiO2 Templated by Non‐Ionic Block Copolymers. Issue 1 (3rd January 2018) - Loreto, Stefano; Vanrompay, Hans; Mertens, Myrjam; Bals, Sara; Meynen, Vera
Abstract : We show the possibility to tune the pore size of mesoporous TiO2 templated by non‐ionic block copolymers by adding different inorganic acids at well‐chosen concentration. The effect of the inorganic anions on both the TiO2 cluster formation and the non‐ionic block copolymers micelles is investigated to explain the experimental results. Abstract : In this work, the use of inorganic acids during soft templating synthesis with non‐ionic copolymers is revealed as an easy possibility to tune the pore size of mesoporous TiO2 . Various inorganic acids in different concentrations are investigated for their effect on pore size and uniformity of distribution. An intertwined effect of pH and anion is clearly visible depending on the acid applied.